Chitosan-Hyaluronate Hybrid Gel Intraarticular Injection Delays Osteoarthritis Progression and Reduces Pain in a Rat Meniscectomy Model as Compared to Saline and Hyaluronate Treatment - Shachar Patchornik; Edward Ram; Noah Ben Shalom; Zvi Nevo; Dror Robinson (Advances in Orthopedics)
Chitosan-Hyaluronate hybrid gel (CHHG) is a self-forming thermo-responsive hydrogel. The current study was undertaken in order to assess the effect of CHHG on rat's surgically induced osteoarthritis. Methods. Thirteen rats were included in the study. In all rats weight-bearing was assessed using a Linton Incapacitance tester. All rats underwent bilateral medial partial meniscectomy. Four rats received a saline injection in the control knee and a 200-microliter injection of CHHG in the experimental knee. Five rats received a high-molecular weight hyaluronate injection to the control knee and a 200-microliter injection of CHHG in the experimental knee. Four rats underwent the same surgical procedure, allowed to recuperate for seven days and then CHHG and hyaluronate were injected. The animals were followed for 6 weeks. Two weeks after injection of a therapeutic substance the amount of weight-bearing on each knee was evaluated using a Linton Incapacitance meter. Results. Two weeks after induction of osteoarthritis there is less pain in the CHHG-treated knee than in the control-treated knee, as determined using a Lintron Incapacitance meter. After six-weeks the histological appearance of the CHHG-treated knee was superior to that of the controls. This is indicated by thicker cartilage remaining on the medial femoral condyle as well as less cyst formation in the CHHG-treated knee. Discussion. CHHG appears to delay progression of osteoarthritis and lessen pain in a rat surgically-induced knee osteoarthritis model. These results support other published results, indicating that there is an ameliorative effect of chitosan on human and rabbit osteoarthritis.